Clinical application of mesenchymal stem cells in immunosenescence: a qualitative review of their potential and challenges - Xu Wang; Dan Guo; Chengmei He; Xiaoxi Wang; Yi Wei; Fengchun Zhang; Li Wang; Yanlei Yang (Stem Cell Research & Therapy)
Abstract Aging leads to a gradual decline in immune function, termed immunosenescence, which significantly elevates the susceptibility to infections, cancers, and other aging-related diseases. Recent advancements have shed light on the molecular underpinnings of immune aging and pioneered novel therapeutic interventions to counteract its effects. Mesenchymal stem cells (MSCs)-a type of multipotent stromal cells with regenerative potential, low immunogenicity, and strong immunomodulatory properties-are increasingly recognized as a promising therapeutic option to reverse or alleviate immunosenescence-related dysfunction. This review systematically summarizes recent discoveries on how MSCs counteract immune aging, particularly their ability to rejuvenate aged immune cells and restore immune homeostasis. It also addresses key challenges, such as variations in MSC sources, donor variability, and the lack of standardized protocols, while proposing future directions to enhance therapeutic precision. Although preclinical and clinical studies highlight the potential of MSC-based strategies for delaying immunosenescence, critical issues remain unresolved, including long-term safety and efficacy, optimizing cell delivery systems, and elucidating context-specific mechanisms. Addressing these challenges will accelerate the development of MSC-based therapies to combat aging-associated immune decline.